The Effect of Job Satisfaction and Gender on the Relationship between Employee Engagement and Intention to Leave in PT X: A Moderated Mediation Analysis - Yeni Risdayanti; Christine Winstinindah Sandroto (AIBPM Publisher, 2020)
This study aims to determine the effect of job satisfaction and gender on the relationship between employee engagement and intention to leave. The population in this study were all employees of PT X. The 121-sample size was determined by Slovin formula. The study used convenience sampling for the sampling technique. The data obtained were analyzed with Simple Mediation Model with Macro Process. The research findings contended that job satisfaction is proven to mediate the relationship between employee engagement and intention to leave which moderated by gender.